Legal Implications of the Concealment of the Origin of Assets in Money Laundering Criminal Offences - Ghifari, Angga Aidry (KnE Social Sciences, 2025)
One of the crimes that often occur in Indonesia is money laundering. The problem that often occurs with perpetrators of money laundering is that they try to hide or disguise assets that are the result of criminal acts in various ways so that they are difficult to trace by law enforcement officers. This study aims to determine and analyze the construction of norms for concealing or disguising the origin of assets in money laundering crimes and to determine and analyze the legal implications of concealing or disguising the origin of assets in money laundering crimes. The approach method used in this study is the normative legal approach. The results of the study show that the regulation of norms on concealment or disguising the origin of assets in money laundering crimes in Indonesian legal provisions has not regulated further in the formulation of how to determine whether a person can be said to have concealed the origin of his assets in committing money laundering crimes, only to the extent of regulating that if a person hides the origin of assets there will be legal consequences, so it is necessary to create a regulation that can accommodate the vacuum of these legal norms in order to achieve legal certainty, one of which is the “follow the money approach” which attempts to find money/property/other wealth that can be used as evidence of the object of the crime.